Implementation of Regional Government Regulation Policies Related to The Development of Super Priority Tourism Destinations: Implementasi Kebijakan Peraturan Pemerintah Daerah Terkait Pengembangan Destinasi Pariwisata Super Prioritas - Adamy, Zulham; Wiradharma, Gunawan (Fakultas Hukum Universitas Jambi, 2024)
Local Government in the development of super priority tourist destinations has a very important role in supporting the success of tourism development. This means that the Regional Government has broader authority for its territory, the implications of the increasing duties and responsibilities to explore and develop all the potential natural resources owned by the region to sustain the regional development journey. With this regulation, the Regional Government has the flexibility to develop its tourism destination. Determining how the Toba Samosir Regency local government has implemented its policy regarding the development of the Lake Toba super-priority destination is the sole objective of this study. This is a qualitative form of research. Communications, resources, disposition, bureaucratic structure, and disposition are the four tenets of policy implementation proposed by Edward's theory, which is the framework utilized. The results of this study indicate that the implementation of the Toba Samosir Regency local government regulation policy in the development of Lake Tiba super priority tourism destinations has been running effectively by the specified policy, although there are still obstacles in several areas such as communication and resources that have not been optimally realized.